Evolución de caries dental a lesión pulpar y periapical en los usuarios que acuden a la clínica odontológica de la Universidad Nacional de Loja 2015. - Flores Cango, Cintia Liliana (2016)
The present study had as object to register the frequency from evolution of dental decays to pulp injury and periapical in the users that flock to the odontologic clinic from the University Nacionaly of Loja 2015, from accord to the gender, age, and dental team. These work, it is from kind quantitative , descriptive, transversal, restrospective and from camp, it is based in the revition from clinics histories clinics from endodontics in number of 237 of wich 164 records demonstrated the precency from decays, by the analysis it is used record collection from data elaborated by the autor. The results had was: the dental decays it is present with higher frequency in the age from 11-25 years, in the periapical injury in the 35% and the pulp on 32%; most afected was the female gender with a 70% pulp injury and 68% the periapical; the dental team more committed ti is the incisor central upper in a 34% from pulp injury and the 39% in the periapical, and the first and second premolar lower in 40% and 38% respectively. It concluded that the dental decays develop to pulp injury and peripical, affecting more the age group from 11-25 years, in the gender female , and in the dental group lower. Keywords: dental decays, gender, age, dental team, pulp injury, periapical injury.